The U.S. Constitution : a very short introduction - Bodenhamer, David J. ([New York] : Oxford University Press, 2018)
This work explores the major themes of American constitutional history - federalism, the balance of powers, property, representation, equality, rights, and security.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 27, 2018).
Keywords: Constitutional history -- United States; Constitutional law -- United States; United States